1999
DOI: 10.1136/bmj.319.7215.943
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural counselling in general practice for the promotion of healthy behaviour among adults at increased risk of coronary heart disease: randomised trial   Commentary: Treatment allocation by the method of minimisation

Abstract: Objective To measure the effect of behaviourally oriented counselling in general practice on healthy behaviour and biological risk factors in patients at increased risk of coronary heart disease. Design Cluster randomised controlled trial. Participants 883 men and women selected for the presence of one or more modifiable risk factors: regular cigarette smoking, high serum cholesterol concentration (6.5-9.0 mmol/l), and high body mass index (25-35) combined with low physical activity. Intervention Brief behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(190 citation statements)
references
References 23 publications
4
180
0
4
Order By: Relevance
“…11 The power of the study was insufficient to detect differences in smoking cessation, although the self-reported reduction in the number of cigarettes smoked was greater in the behavioral intervention group. The present results corroborate these differences in behavioral response by demonstrating that the likelihood of attaining the target stage of change in fat intake and physical activity was greater for the behavioral intervention group than for the control group at both 4 months and 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The power of the study was insufficient to detect differences in smoking cessation, although the self-reported reduction in the number of cigarettes smoked was greater in the behavioral intervention group. The present results corroborate these differences in behavioral response by demonstrating that the likelihood of attaining the target stage of change in fat intake and physical activity was greater for the behavioral intervention group than for the control group at both 4 months and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The behavioral and biological risk factor results of this study, which have been described elsewhere, show greater reductions in fat intake and the number of cigarettes smoked and greater increases in physical activity in the behavioral intervention group than in the control group at 4 and 12 months. 11 In this article, we present stage of change outcomes in the study and address (1) whether behavioral intervention was more effective than normal practice in achieving the target stage (action/maintenance), (2) whether the likelihood of achieving the target stage for each behavior varied with initial stage, and (3) whether any advantage of behavioral intervention was equally evident for patients at different stages of readiness at baseline.…”
mentioning
confidence: 99%
“…Tailoring nutrition counselling to the stages of change has been suggested to increase programme effectiveness (Ashworth, 1997;Kristal et al, 1999;Steptoe et al, 1999Steptoe et al, , 2001. Although some studies have shown favourable results of stage-matched nutrition counselling (Campbell et al, 1994;Steptoe et al, 1999Steptoe et al, , 2001Tilley et al, 1999;Van der Veen et al, 2002), the principle of stage-matched approaches in nutrition counselling is not undisputed.…”
Section: The Stages Of Change Model For Nutrition Counsellingmentioning
confidence: 99%
“…In a short (two or three counseling sessions) lifestyle intervention in England in almost 900 men and women 25 , after 12 months, lifestyle was still improved (dietary fat intake, regular exercise and cigarettes smoked per day) but there was no difference in levels of biological risk factors (blood pressure, body weight and serum cholesterol) between the intervention group and control group.…”
Section: Effects In Individuals With Varying Combinations Of Risk Facmentioning
confidence: 98%